MANAJEMEN KEUANGAN SEKOLAH - Ghazali Adillah (Manajer Pendididikan, 2016)
The objectives of this research were to describe the management of school finance at Junior High School number 1 Tebat Karai, Kepahiang Regency. The research method wasdescriptive qualitative. The subject of this research are principal, administration staff, teachers, school committee and treasurer. The data were collected by interview, observations anddocumentations. The result of this research show that school finance was begun by designing of planning and school finance. The main problem was limited for principal to manage some budgets in all activities at school. To design planning and school finance, principal together with school committee, teacher representatives, treasure to define allocation of school budgets.Keywords: management, school finance